PENGARUH PERDAGANGAN INTERNASIONAL EKSPOR DAN IMPOR TERHADAP PEREKONOMIAN INDONESIA - Muhammad Vito Prasetiyo; Muhamad Ripqi; Apriliantoni, Apriliantoni (Cahaya Ilmu Bangsa, 2025)
International trade has a significant influence on the Indonesian economy. This analysis shows that international trade increases economic growth, prosperity, and economic stability. Increasing exports of high-quality products to international markets drives Indonesia's economic growth, increases national income and creates jobs. International trade also increases access to goods and services, transfer of technology and knowledge. However, international trade also has challenges such as competition from the quality of imported products which can affect the domestic industry.